Integrating gut microbiota into multidisciplinary perspectives on diabetic neuropathy - Horiachok, Maksym; Potapova, Kateryna; Ivanykovych, Taras; Yerokhovych, Viktoria; Ilkiv, Yeva; Sokolova, Larysa (Frontiers in Endocrinology, 2025)
Diabetic neuropathy (DN) is one of the most common and debilitating complications of diabetes mellitus, yet its precise pathogenesis remains incomplete. Emerging evidence highlights the gut microbiome as a key factor linking metabolic dysfunction, immune activation, and neuronal damage. Even minor dysbiosis may interfere with microbial metabolite balance and disrupt intestinal integrity, leading to local and, consequently, systemic inflammation, which in turn drives altered pain response via the gut-brain-immune axis. Recent clinical and preclinical data show that reduced short-chain fatty acid availability, altered bile acid and tryptophan metabolism, let alone expansion of pro-inflammatory species collaboratively contribute to DN onset and progression. Moreover, advances in metagenomics and metabolomics reveal reproducible microbiome-derived biomarkers that could predict neuropathy risk and pain phenotypes independent of glycemic control, supporting the microbiome as both a mechanistic driver and a measurable potential diagnostic tool. In the context of management, microbiota-affected interventions, such as probiotics, synbiotics, omega-3 supplementation, and fecal microbiota transplantation, show early promise in alleviating symptoms and improving nerve function. This mini-review synthesizes current evidence on the microbiome’s role in DN, emphasizing its dual potential as a biomarker for early diagnosis and a therapeutic target for precision microbiome-based interventions.